PENGARUH KOMITE AUDIT, STRUKTUR MODAL, DAN PERTUMBUHAN ASET TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan yang terdaftar di BEI Tahun 2016-2020) - Tiriwanti Sagala; Putri Nurmala (Universitas Mataram, 2021)
This study aims to analyze and provide empirical evidence of the effect of the audit committee,capital structure, and asset growth on company performance. This type of research is quantitative descriptive using secondary data that can be accessed through the Indonesia Stock Exchange website. This study uses three independent variables and one related variable. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period, totaling 44 companies. The sample selection procedure was carried out by purposive sampling method, only 22 companies had criteria with an observation period of 5 years,so the number of samples for this study was 110 observations. The data analysis technique used is multiple linear regression analysis, descriptive statistics, classical assumption test. selection of panel data regression model, test the coefficient of determination (R2) and test the hypothesis by using the eviews 9 program data processing. The results of this study state that based on the F test, the audit committee variables, capital structure and asset growth simultaneously have a significant effect on company performance. Partially, the asset growth variable has a significant effect on the company's performance. Meanwhile, the audit committee and capital structure have no significant effect on the company's performance.